Heterogeneous enantioselective synthesis of chromans via the oxa-Michael–Michael cascade reaction synergically catalyzed by grafted chiral bases and inherent hydroxyls on mesoporous silica surface. Issue 63 (24th July 2017) - Wang, Shanshan; He, Jing; An, Zhe
Abstract : A heterogeneous enantioselective oxa-Michael–Michael reaction for the synthesis of chromans has been developed on bifunctional catalysts, resulting in excellent catalytic performance. Abstract : A heterogeneous enantioselective oxa-Michael–Michael reaction for the synthesis of chromans has been developed on a heterogeneous acid–base synergic catalyst with inherent silica as acidic sites and immobilized chiral amines as basic sites. Final products were afforded in selectivity of up to 98% and ee of 97% from 2-nitrovinyl phenol and 3-methyl-2-butenal. The heterogeneous synergistic catalytic mechanism has also been studied.